Adding Value to Malta's Youth Travel through Innovation Case Study: NSTS Student and Youth Travel, Malta - Keith, Caruana (2006)
In recent years innovation has gained significant importance particularly due to the increasing competition companies and organisations are facing. This competition is threatening the economic stability of Western economies. Innovation is the only key that enables companies and organisations to be distinguishable from others which are operating in the same market and probably producing the same product or service. This is widely seen in the travel and tourism industry where the services are more or less identical. However, through innovation, organisations add an extra element to their core product and thus become distinguishable from others.